Blockchain-based distributed frequency control of sustainable networked microgrid system with P2P trading - Irudayaraj, Andrew Xavier Raj (2024)
In this work, proof of Authority (PoA)-based Ethereum blockchain is utilized to carry out the peer-to-peer (P2P) energy transactions with an adaptive controller operating in a distributed manner. A federated average learning of recurrent zeroing neural dynamics designed self-adaptive fractional-order proportional integral derivative (FAL-ZND FOPID) controller is proposed for distributed frequency control of networked microgrid (NMG) system. By employing a blockchain-enabled distributed control system and implementing supplementary control, the proposed method efficiently regulates the frequency of P2P energy trading. The contract participation matrix, which facilitates the transmission of energy demand information from consumers to prosumers, is computed as part of the supplementary control. Thus, it provides the power reference signals to prosumers who participate in ancillary frequency services. Overall, the blockchain implementation ensures that the transfer of signals remains secure from cyber threats. To showcase this concept, the prosumer and consumer nodes are established within the blockchain network using Raspberry Pi devices. These devices are then connected to the NMG setup in OPAL-RT through the socket interface and communicate via TCP/IP protocol.